Developing an environmental education strategy framework: a case study of the Endangered Wildlife Trust (EWT) - O'Grady, Janis (Rhodes University, Faculty of Education, Department of Education, 2005)
The study focused on the development of an environmental education (EE) strategy framework in the Endangered Wildlife Trust (EWT) of South Africa. Evidence shows that the roles of conservation and biodiversity education could potentially be merged towards producing a practical strategy, beneficial to the organisation and its individual staff members. Questionnaires, interviews and the individual perceptions of staff members, as well as the analysis of relevant documents, suggested that the potential for the practice of EE towards the development of an EE strategy within the organisation is substantial. EWT staff members can contribute towards a change in the way that South Africans think about conservation and nature. Environmental ethics need to be promoted and understood by all. Within the EWT, environmental education activities are in place and diverse, yet they lack any form of monitoring and evaluation. The Trust is already practicing a form of EE but the potential to do more and the opportunities for expansion are unlimited.
Keywords: Endangered Wildlife Trust; Environmental education -- South Africa; Conservation of natural resources -- South Africa; Biodiversity -- South Africa